The Liberal Diplomacy of Joaquim Nabuco - Rosi, Bruno Gonçalves (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
Besides his career as an abolitionist, intellectual, writer and historian, Joaquim Nabuco had also an important, although short, diplomatic career. His main contribution in this respect was changing the Brazilian diplomatic axis from Europe to the U.S. Usually, this gesture is credited to Barão do Rio Branco, but far from just supporting this decision, Nabuco was an important formulator of Brazilian Foreign Policy. His view of international politics was in tune with his previous political work, showing a liberal optimism that is absent in the Barão.